Pengaruh Pemberian Bahan Pembenah Tanah Terhadap Kemampuan Hidup Bidara Laut Strychnos lucida R. Br. Di Taman Wisata Alam Gunung Tunak Nusa Tenggara Barat - Ali Setyayudi; Ryke Nandini; Krisnawati Krisnawati (Faculty of Forestry Universitas Gadjah Mada, 2023)
Bidara Laut (Strychnos lucida R.Br.) has the potential as a medicinal plant in West Nusa Tenggara, but its cultivation encountered many challenges. Mount Tunak, Natural Tourism Park, had similar environmental conditions to the natural habitat of Strychnos lucida and was selected as the location for planting trials. Given the dry climate, high temperature, and soil fertility limitations, the trials applied soil amendments, such as hydrogel, mycorrhizae, mulch, and fertilizer, to enhance the growth. This research aimed to investigate the effects of soil amendments on the survival rate of Strychnos lucida. This research used a Randomized Complete Block Design (RCBD) with four treatments and one control. The treatments included applying five grams of hydrogel, five grams of mycorrhizae, 1 m x 1 m of plastic mulch, and a combination of all three. The research used 15 replication blocks, each with an area of 450 m2 and a spacing of 3 m x 3 m. Each block included ten replication plants (in total 750 plants), and the trial lasted 19 months. The results showed an insignificant growth increase after 19 months of planting in all treatments. There were improvements in survival rate, height growth, and diameter growth by 25%, 85%, and 25%, respectively.